2021
DOI: 10.1101/2021.01.26.428255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The regulatory landscape of the human HPF1- and ARH3-dependent ADP-ribosylome

Abstract: SUMMARYDespite the involvement of Poly(ADP-ribose) polymerase-1 (PARP1) in many important biological pathways, the target residues of PARP1-mediated ADP-ribosylation remain ambiguous. To explicate the ADP-ribosylation regulome, we analyzed human cells depleted for key regulators of PARP1 activity, histone PARylation factor 1 (HPF1) and ADP-ribosylhydrolase 3 (ARH3). Using quantitative proteomics, we quantified 1,596 ADPr sites, displaying a thousand-fold regulation across investigated knockout cells. We find t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 65 publications
3
18
0
Order By: Relevance
“…Combined with previous findings ( Abplanalp et al., 2017 ; Fontana et al., 2017 ; Hanzlikova et al., 2020 ; Hendriks et al., 2021 ; Palazzo et al., 2018 ), our data confirm that ARH3 is the main hydrolase of endogenous serine-linked MAR ( Figures 6 A and 6B), while PARG swiftly removes long PAR chains ( Figures 6 A and 6C) that are composed largely of PARP1 autoPARylation in an unstressed environment but could also come from the DNA replication-associated events, namely unligated Okazaki fragments ( Hanzlikova et al., 2018 ). Critically, whereas elevated MARylation in ARH3-deficient cells is well tolerated, combined ARH3 deficiency and PARG suppression results in the accumulation and persistence of PARylation that is highly toxic to the cell and has distinct (patho)physiological effects ( Figure 6 D).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Combined with previous findings ( Abplanalp et al., 2017 ; Fontana et al., 2017 ; Hanzlikova et al., 2020 ; Hendriks et al., 2021 ; Palazzo et al., 2018 ), our data confirm that ARH3 is the main hydrolase of endogenous serine-linked MAR ( Figures 6 A and 6B), while PARG swiftly removes long PAR chains ( Figures 6 A and 6C) that are composed largely of PARP1 autoPARylation in an unstressed environment but could also come from the DNA replication-associated events, namely unligated Okazaki fragments ( Hanzlikova et al., 2018 ). Critically, whereas elevated MARylation in ARH3-deficient cells is well tolerated, combined ARH3 deficiency and PARG suppression results in the accumulation and persistence of PARylation that is highly toxic to the cell and has distinct (patho)physiological effects ( Figure 6 D).…”
Section: Discussionsupporting
confidence: 89%
“…Subcellular fractionation following cell cycle synchronization confirmed these observations ( Figures S1 A and S1B). The signals were lost upon small interfering RNA (siRNA)-mediated HPF1 knockdown ( Figures S1 C–S1E), which together with a recent mass spectrometry study ( Hendriks et al., 2021 ) confirms that ADPr in ARH3-KO U2OS cells is specifically enriched at serine residues.
Figure 1 Loss of ARH3 leads to the enrichment of chromatin-associated MARylation throughout the cell cycle (A) Cells were subjected to subcellular fractionation.
…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Those and similar peptides and proteins carrying different ADP-ribose-like units indeed enabled the successful generation of several polyclonal ADP-ribose-recognizing antibodies [127,155]. A comparison between some of these antibodies and the macrodomain Af1521 commonly used for MS analysis, however, revealed that for those analysis, the macrodomain still outperforms the antibodies [174]. Nonetheless, while the new antibodies recognize MAR and PAR and therefore are referred to as pan-ADP-ribose antibodies, they could already be used to study organelle and mono-ART-specific ADP-ribosylation dynamics by Western blotting (WB) and Immunofluorescence (IF) in different contexts [127,175].…”
Section: Antibodies Against Mar And/or Parmentioning
confidence: 99%